2010
DOI: 10.2169/internalmedicine.49.3173
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in Transcatheter Treatment of Hepatocellular Carcinoma: an Open Randomized Prospective Study of Oral Versus Intravenous Administration

Abstract: Background Transcatheter arterial chemoembolization (TACE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…It seems that prophylactic antibiotic treatment is necessary as the fatal infection may exist in HCC patients with the background of HBV and cirrhosis which means the decreased resistance to bacterial infection because of the hepatic functional damage, leukopenia and so on. 18 Reviews in 2017 pointed that the antibiotics is necessary and beneficial even in the absence of risks described above. 4 The primary mechanism for infection was thought most likely contamination of the embolized segment of hepatic parenchyma with biliary pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that prophylactic antibiotic treatment is necessary as the fatal infection may exist in HCC patients with the background of HBV and cirrhosis which means the decreased resistance to bacterial infection because of the hepatic functional damage, leukopenia and so on. 18 Reviews in 2017 pointed that the antibiotics is necessary and beneficial even in the absence of risks described above. 4 The primary mechanism for infection was thought most likely contamination of the embolized segment of hepatic parenchyma with biliary pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…[14] However, other studies have demonstrated that prophylactic antibiotics do not need to be administered to patients prior to TACE. [15,16] Unnecessary antibiotic usage has several potential risks, such as alteration of the intestinal flora and an increase in antibiotic resistance and hospital cost. Here, we report a rare case of hepatic abscess combined with polymicrobial bacteremia in a patient with a history of radical pancreaticoduodenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Many institutes still prescribe antibiotics routinely to patients with fever after TACE or RFA [ 22 , 26 ]. Some even recommend the use of prophylactic antibiotics despite a low incidence of infectious complications [ 27 ], probably because infections in patients with impaired liver function often lead to fatal outcomes. However, this excessive antibiotic use also leads to the emergence of antibiotic resistance, increased medical costs, and adverse effects of antibiotics.…”
Section: Discussionmentioning
confidence: 99%